Online Deliberation and the Public Sphere: Developing a Coding Manual to Assess Deliberation in Twitter Political Networks - Esteve Del Valle, Marc; Sijtsma, Rimmert; Stegeman, Hanne; Borge, Rosa (Javnost-The Public, 2020)
To what extent are elements of rational-critical debate present in Twitter political networks? And to what extent are the discursive practices in these networks constitutive of a public sphere online? This research presents the different phases of a coding manual we developed to assess deliberation in Twitter political networks. To exemplify the use and value of the coding manual, we manually annotated communications (N = 3657) in the Dutch MPs’ mentions Twitter network. Our results show clear signs of positive empathy and cross-ideological interactions in the MPs’ communications, yet they also point to low levels of internal justification, reflexivity and critique. Therefore, although communications in the Dutch MPs’ mentions Twitter network exhibit important components of rational-critical debate, they cannot be considered full-fledged deliberative.